Both/and thinking embracing creative tensions to solve your toughest problems - Smith, Wendy K.; Lewis, Marianne W. (Harvard Business Review Press, 2022)
"Life is full of paradoxes. How can we each express our individuality and be a team player? How do we balance work and life? How can we take care of ourselves while supporting others? How can we manage the core business while innovating for the future? For many of us, these competing and interwoven demands are a source of conflict. Since our brains love to make either-or choices, we choose one option over the other. We deal with the uncertainty by asserting certainty. There's a better way. In Both/And Thinking, Wendy Smith and Marianne Lewis help readers cope and thrive with multiple, knotted tensions at the same time. Drawing from more than twenty years of pioneering research, they provide an actionable framework for transforming these tensions into opportunities for innovation and personal growth. Filled with practical advice, groundbreaking research, and fascinating stories, Both/And Thinking will completely change the way you approach your most vexing problems
Includes bibliographical references and index
Keywords: Problemlösen; Unternehmenserfolg; Entscheidungsverhalten; Kreativität; Multiple criteria decision making; Creative ability in business; Choice (Psychology); Problem solving; Success in business; Choice Behavior; Problem Solving; Décision multicritère; Créativité dans les affaires; Choix (Psychologie); Résolution de problème; Succès dans les affaires